Pendampingan Pembukuan Sederhana Pada UMKM di Padukuhan Kauman - Ani Widiawati; Endang Sri Utami (LPPM STIKOM Tunas Bangsa, 2023)
The aim of this service activity is to educate and increase the understanding of MSME actors regarding the importance of accounting knowledge in preparing financial reports and bookkeeping in a business. This service is carried out because many MSMEs only make financial reports conventionally and do not record them regularly. With limited accounting knowledge, accounting processes that are considered complicated, and the perception that structured financial reports are not important for MSME players, the effort to record bookkeeping becomes a big problem for MSME players. The service activity is in collaboration with two MSME partners in the trade sector, namely the Clontong Shop. The problem-solving method begins with interviews, carrying out activities, and evaluating. The assistance medium used is the Kwarto Kas Book. The results of the service show that each partner has a basic understanding of the process of recording transactions, making financial reports, and making transaction input for cash receipts and disbursements.